Formation of 1D hierarchical structures composed of Ni3S2 nanosheets on CNTs backbone for supercapacitors and photocatalytic H2 production - Zhu, Ting (2013)
One-dimensional (1D) hierarchical structures composed of Ni3S2 nanosheets grown on carbon nanotube (CNT) backbone (denoted as CNT@Ni3S2) are fabricated by a rational multi-step transformation route. The first step involves coating the CNT backbone with a layer of silica to form CNT@SiO2, which serves as the substrate for the growth of nickel silicate (NiSilicate) nanosheets in the second step to form CNT@SiO2@NiSilicate core-double shell 1D structures. Finally the as-formed CNT@SiO2@NiSilicate 1D structures are converted into CNT-supported Ni3S2 nanosheets via hydrothermal treatment in the presence of Na2S. Simultaneously the intermediate silica layer is eliminated during the hydrothermal treatment, leading to the formation of CNT@Ni3S2 nanostructures. Because of the unique hybrid nano-architecture, the as-prepared 1D hierarchical structure is shown to exhibit excellent performance in both supercapacitors and photocatalytic H2 production.